A Compact UWB Diversity Antenna - Hui Zhao; Fushun Zhang; Chunyang Wang; Jiangang Liang (International Journal of Antennas and Propagation)
A compact printed ultrawideband (UWB) diversity antenna with a size of 30 mm × 36 mm operating at a frequency range of 3.1–10.6 GHz is proposed. The antenna is composed of two semielliptical monopoles fed by two microstrip lines. Two semicircular slots, two rectangular slots, and one stub are introduced in the ground plane to adjust the impedance bandwidth of the antenna and improve the isolation between two feeding ports. The simulated and measured results show that impedance bandwidth of the proposed antenna can cover the whole UWB band with a good isolation of < −15 dB. The radiation patterns, peak antenna gain, and envelope correlation coefficient are also measured and discussed. The measured results show that the proposed antenna can be a good candidate for some portable MIMO/diversity UWB applications.